Learning Loss dan Ketimpangan Akses STEM Pasca Pandemi COVID-19: Tinjauan Literatur Sistematis - Fathoroni, Fathorroni; Imran, Imran; Rahmatullah, Rahmatullah (Indonesian Publication Center, 2022)
The COVID-19 pandemic has caused significant disruption to the global education system, particularly in STEM education, which requires direct interaction and experimental practice. This study aims to examine the phenomena of learning loss and the digital divide in post-pandemic STEM education and to identify recovery strategies. The method employed is a systematic literature review (SLR) using the PRISMA approach, focusing on peer-reviewed articles from 2020–2022 retrieved from Scopus, Web of Science, and Google Scholar. The findings indicate that learning loss has occurred significantly, particularly in mathematics, and has been exacerbated by technological access disparities, leading to a widening gap in learning outcomes. The interaction of these two factors gives rise to learning inequality, which has the potential for long-term impacts on the quality of human resources in the STEM field. Therefore, comprehensive recovery strategies are needed through strengthening technology access, adapting competency-based curricula, utilizing educational technology, and implementing targeted interventions for vulnerable groups.